Barriers to the Diffusion of Combined Heat and Power (CHP) Technology in Canada - Ottaway, Allan (Université d'Ottawa | University of Ottawa, 2009)
Combined heat and power (CHP) production technology, also known as cogeneration, can yield tremendous efficiency gains compared to the independent production of each. These efficiency gains resutl not only in fuel savings, but greenhouse gas (CHG) emissio